The validity of state contracts arbitration: A law and economics perspective - Guevara-Bernal, Iván (Pontificia Universidad Javeriana, 2013)
This article addresses the nature of state entities participation in commercial contracts where the parties have agreed that any disputes arising from such contracts will be resolved by international arbitration. It will be argued that such participation is preeminently of an economic nature, irrespective of the hybrid character of the legal regime applying to the parties and/or the contracts involved. From this it follows that any conflict that leads to the application of an arbitral clause is also economic and should be apprehended as such even in a legal context. We believe that an understanding of the economic nature of the role played by the state when entering into contractual arrangements of a commercial kind will help to dispel doubts about the arbitrability of conflicts resulting from such arrangements, which the traditional approach of contemplating such arrangements in terms of public/private law has singularly failed to do.After describing the aforementioned traditional approach, we shall propose elements for an economic approach capable of transcending the dichotomy between the public law principles governing state entities and the well-established duty to respect freely and validly agreed commercial contracts. By presenting the state as an economic actor, we shall attempt to provide a better understanding of the legal nature of its participation in commercial contracts, including its capacity to enter into contracts containing arbitration clauses. Taking this argument further, we shall go on to considerthe economic nature of the contractual failings that lead to conflicts, drawing a connection between the economic concepts of externalities and property rights and a juridical understanding of conflicts. While the fundamental purpose of any system of conflict resolution is the redistribution of legal rights, this is materialized in the reallocation of economic resources. Arbitration therefore is not only a legal but also an economic tool, whose role is to ensure that the needs initially expressed through the conclusion of a contract are correctly satisfied in accordance with the terms agreed bythe parties. Seen in this light, arbitration will hopefully appear less of a threat in countries such as Colombia, where part of the economy has been deprived of its benefits, to the detriment of international trade.